Modeling Mesoscale Eddies Generated Over the Continental Slope, East Antarctica - Zhang, Li; Liu, Chengyan; Sun, Wenjin; Wang, Zhaomin; Liang, Xi; Li, Xiang; Cheng, Chen (Frontiers in Earth Science, 2022)
Mesoscale eddies are abundant over the Antarctic continental slope, with the potential to regulate the water masses transport, mixing, and energy transfer. Over the relatively cold and fresh shelf regions around the Antarctic margins, in the absence of dense overflows, the baroclinic instability of the Antarctic Slope Current is still favorable in the generation of mesoscale eddies. However, mesoscale eddies are barely observed over the fresh shelf regions due to the sparsity of in situ hydrographic observations. Based on an idealized eddy-resolving coupled ocean-ice shelf model, this study investigates the characteristics of mesoscale eddies and corresponding influences on the local hydrographic properties over the continental slope, East Antarctica. With the aid of an automated eddy detection algorithm, bowl-shaped eddies are identified from the simulated velocity vector geometry. The Cyclonic Eddies (CE) has a barotropic vertical structure extending to more than 2500 m depth, while the vertical shear of the Anticyclonic Eddies (AE) velocity is strong at the upper 200 m layer. Mesoscale eddies can trap the cold and fresh water in the southern flank of the Antarctic slope front and flow offshore to the relatively warm and saline region. Therefore, the influences of eddies on the hydrographic properties are not only governed by the eddy polarities but also the eddy-induced heat and salt transport. The cores of CE have larger horizontal extension than that of the AE, with relatively uniform anomalies within ~0.5 radius, while the influences of the AE cores decrease linearly with the distance from the eddy centers.